Synthesis of nanosized TiO2 powder by sol gel method at low temperature - Nachit, W.; Touhtouh, S.; Ramzi, Z.; Zbair, M.; Eddiai, A.; Rguiti, M.; Bouchikhi, A.; Hajjaji, A.; Benkhouja, K. (Molecular Crystals and Liquid Crystals, 2016)
Nanotechnology is all about making products from very small constituents, components or subsystems to gain greatly enhanced material properties and functionality. Nanocrystalline anatase TiO 2 was prepared by a facile sol-gel route at a temperature of 50°C under mild conditions. Titanium tetraisopropoxide (TTIP) was used as a titanium precursor, and 2-propanol was used as a solvent. XRD, TEM, SEM, FT-IR and BET were applied to characterize the crystal phase. The Crystalline size of TiO 2 powder has been obtained with diameter < 30 nm for anatase at 500°C using an acid.